VISTA Deficiency Accelerates the Development of Fatal Murine Lupus Nephritis - Ceeraz, Sabrina (Arthritis Rheumatol, 2017)
OBJECTIVE: The targeting of negative checkpoint regulators as a means of augmenting antitumor immune responses is now an increasingly used and remarkably effective approach to the treatment of several human malignancies. The negative checkpoint regulator VISTA (V-domain Ig–containing suppressor of T cell activation; also known as programmed death 1 homolog or as death domain 1α) suppresses T cell responses and regulates myeloid activities. We proposed that exploitation of the VISTA pathway is a novel strategy for the treatment of human autoimmune disease, and therefore we undertook this study to determine the impact of VISTA genetic deficiency on lupus development in a lupus-prone mouse strain. METHODS: To evaluate whether genetic deficiency of VISTA affects the development of lupus, we interbred VISTA-deficient mice with Sle1.Sle3 mice, a well-characterized model of systemic lupus erythematosus (SLE). RESULTS: We demonstrated that the development of proteinuria and glomerulonephritis in these mice, designated Sle1.Sle3 VISTA(−/−) mice, was greatly accelerated and more severe compared to that in Sle1.Sle3 and C57BL/6 VISTA(−/−) mice. Analysis of cells from Sle1.Sle3 VISTA(−/−) mice showed enhanced activation of splenic CD4+ T cells and myeloid cell populations. No increase in titers of autoantibodies was seen in Sle1.Sle3 VISTA(−/−) mice. Most striking was a significant increase in proinflammatory cytokines, chemokines, and interferon (IFN)–regulated genes associated with SLE, such as IFNα, IFNγ, tumor necrosis factor, interleukin-10, and CXCL10, in Sle1.Sle3 VISTA(−/−) mice. CONCLUSION: This study demonstrates for the first time that loss of VISTA in murine SLE exacerbates disease due to enhanced myeloid and T cell activation and cytokine production, including a robust IFNα signature, and supports a strategy of enhancement of the immunosuppressive activity of VISTA for the treatment of human lupus.